FAUNA DE COLEOPTERA MELOLONTHIDAE Y PASSALIDAE DE TZUCACAB Y CONKAL, YUCATÁN, MÉXICO - Reyes Novelo, Enrique; Morón, Miguel Ángel (Instituto de Ecología, A.C., 2005)
A study of the Melolonthidae and Passalidae beetle fauna of Conkal and Tzucacab, Yucatan, Mexico is presented. Data from 6,378 specimens were obtained during 2001-2002 with 74 days of collecting effort in tropical deciduous forest and secondary vegetation, located between 9-70 m of altitude. Forty nine species of the genera Phyllophaga, Diplotaxis, Anomala, Chasmodia, Macraspis, Plesiorutela, Pelidnota, Cyclocephala, Ligyrus, Strategus, Coelosis, Phileurus, Gymnetis, Cotinis, Hoplopyga, Balsameda, Amithao, Euphoria, Trigonopeltastes, Passalus, Heliscus and Verres, are recorded. Species were more abundant in April, May and June. Most of them were from Conkal, but higher species richness was found in Tzucacab. Eighteen species are reported for the first time from Yucatan State. Hoplopyga ocellata G. & P. and Euphoria subguttata Burmeister are confirmed as part of the Mexican fauna. A key to the 49 species, as well as comparative data between scarab beetle fauna of Tzucacab, Conkal and other tropical localities of Mexico, are included. Some biogeographically, agricultural and conservational aspects of these fauna are briefly discussed.